Are they buying or selling again?: Estimating the impact of neighborhood-level contagion on types of juvenile drug recidivism - Lockwood, Brian (Crime & delinquency, 2019)
We examine how the densities of adult and juvenile drug offenders within neighborhoods might be linked to the odds of juvenile recidivism due to drug sales and drug possession. To do so, we analyze a dataset of 5,528 juvenile offenders adjudicated in Philadelphia’s Family Court between 1996 and 2004 using multilevel models to estimate the effects of both individual- and neighborhood-level indicators on the odds of recidivism. The results indicate that community context is significantly related to the odds of juvenile recidivism due to drug sales, but not due to drug possession. Neighborhood levels of adult and juvenile drug offender densities are also shown to moderate the links between individual-level characteristics and the odds of juvenile drug sales recidivism.